2017
DOI: 10.1080/02699052.2017.1374467
|View full text |Cite
|
Sign up to set email alerts
|

Pre-injury psychosocial and demographic predictors of long-term functional outcomes post-TBI

Abstract: Pre-injury psychosocial and demographic factors may be more important than injury severity for predicting some long-term functional outcomes post-TBI. It would likely be beneficial to assess these factors in the inpatient setting, with input from a multidisciplinary team, as an early understanding of prognostic indicators can help guide treatment for optimal functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This is in accordance with previous mixed sample studies [11,13,16,17] of the predictive value for cause of injury, but in contrast to previous studies [11e13, 16,17] for the predictive value of GCS on the level of activities and participation in samples of children with mixed TBI-severity. A previous study on long-term functional outcomes post-TBI in adults found that GCS was significantly related to mobility, but not cognitive and physical independence or occupation and social integration [38]. Since mobility is more often affected in patients with lower GCS scores, the predictive value of GCS is possibly more prominent in more severe TBI's in comparison to mTBI.…”
Section: Discussionmentioning
confidence: 87%
“…This is in accordance with previous mixed sample studies [11,13,16,17] of the predictive value for cause of injury, but in contrast to previous studies [11e13, 16,17] for the predictive value of GCS on the level of activities and participation in samples of children with mixed TBI-severity. A previous study on long-term functional outcomes post-TBI in adults found that GCS was significantly related to mobility, but not cognitive and physical independence or occupation and social integration [38]. Since mobility is more often affected in patients with lower GCS scores, the predictive value of GCS is possibly more prominent in more severe TBI's in comparison to mTBI.…”
Section: Discussionmentioning
confidence: 87%
“…People with TBI experience physical, behavioral, emotional, and cognitive difficulties that can persist many years after injury [20,21] and affect many aspects of everyday living, including independence, mobility, employment, and community integration [22]. Social and interpersonal skills are among the most notable impairments and have been shown to interfere with community living, occupational status, and sustainment of interpersonal relationships [23,24].…”
Section: Functional Outcomes Following Tbimentioning
confidence: 99%
“…A longitudinal, prospective study of psychological and demographic factors associated with TBI outcomes found that pre-injury psychiatric history and education are associated with life satisfaction. 83 Seagly et al 84 observed that long-term post-TBI functional outcomes were predicted by cognitive and physical independence more than age at injury and Glasgow Coma Scale (GCS) score. Bertisch et al 85 found that, whereas individuals with TBI either with or without psychiatric histories did not show a difference in treatment, return to work delay, or social activity, TBI patients with psychiatric history did display slower processing speed and less satisfaction with their work.…”
Section: The “Life Effect”mentioning
confidence: 99%